131 Preanalysis nonconformities management in a routine medical laboratory. (23rd September 2015) - Fischer, F; Appert-Flory, A; Raynaud, S; Quaranta, J F; Levraut, J; Fuzibet, J G
Abstract : Introduction: The preanalytic process is a crucial step for the accuracy of results in a routine medical laboratory. It also has a forensic weight. We report a continuous improvement of the quality process in the management of nonconformities in the preanalytical sector of the Haematology laboratory of the CHU of Nice. Brief Outline of Context: Main preanalytical nonconformities (NC) observed in our laboratory in 2007 was collected retrospectively. 169 244 adverse events were recorded, (including lack of date/time of blood collection (n=81269), antithrombotic treatment not specified (n=87753), lack of specimen identification (n=93), inadequate filling (n=100) coagulated blood samples (29)), and analysed using the RCA method. After assessment of the problem and analysis of its cause, we identified and applied some improvement actions. Goal: To reduce the two most frequent adverse events observed in our laboratory: Adverse event #1: lack of date/time of blood collection (hour and day) (81 269 over 230 476 received prescription forms (35%)) Adverse event #2: antithrombotic treatment not specified. (87 753 over 166 016 received haemostasis prescription forms (53%)) Our goal was to reduce the global monthly percentages to less than 15% for both items. Strategy for Change: We chose two medical departments interested in this approach: the adult emergency department and the department of internal medicine. The corrective actions consisted in meetings with the staff of the two departments (physicians and nurses), to form and inform them on the importance to correctly fulfil the laboratory prescription forms, and the consequences of incomplete data on laboratory results quality. During the successive meetings with the staff of both departments (1 per month from January 2008 to June 2008), follow-up of NC percentages was provided and analysed. Measurement of Improvement and Effects of Changes: The monthly follow-up of the NC percentages for the two departments involved in the study is reported below: Adverse event #1 adult emergency department: month 1 (32%), month 12 (27%), month 24 (18%) internal medicine department: month 1 (45%), month 12 (27%), month 24 (6%) Adverse event #2 adult emergency department: month 1 (41%), month 12 (45%), month 24 (40%) internal medicine department: month 1 (75%), month 12 (85%), month 24 (75%) Results: Adverse event #1: dramatic improvement in compliance with prescription form fulfilment, sustained in 2009 Adverse event #2: we didn't notice any stable improvement on the NC. We have to develop new corrective actions, maybe based on computerised prescription with the obligation to give information about the treatments. Lessons learned and conclusion: Providing objective data is effective in convincing physicians and nurses of the need for change. Continuous follow-up is essential to ensure that changes are fully implemented. Increased sensitivity of the staff to correct errors was not sufficient to reduce the percentage of adverse event #2. To be successful, the RCA method needs an exhaustive analysis of the root causes. Introduction: Le processus pré-analytique est une étape cruciale pour la justesse du rendu des résultats dans un laboratoire d'analyses médicales. Il revêt également un enjeu médico-légal. Nous rapportons le processus d'amélioration continue mis en place dans le laboratoire d'hématologie du CHU de Nice concernant la gestion des NC de l'étape pré-analytique. Etat des lieux: Les types et les pourcentages de NC du processus pré-analytique tracés dans le laboratoire en 2007 ont été collectés rétrospectivement. Ainsi, 169244 NC ont été enregistrés [dates et heures de prélèvement non renseignées (n=81269), traitement non renseigné (n=87753), erreur d'identification de l'échantillon (n=93), trait de jauge non respecté (n=100), prélèvement coagulé (29)] et analysés en utilisant la méthode RCA. Après évaluation des dysfonctionnements et analyse des causes, nous avons identifié et mis en place des actions d'amélioration. Objectif: Diminuer le nombre des NC les plus fréquemment rencontrées dans le laboratoire: elles concernent essentiellement l'absence de renseignement des bons de demande sur 2 critères: critère #1 « dates et heures de prélèvement non renseignée » [81269 sur 230476 bons de demande (35%)] et critère #2 « traitement anticoagulant non renseignée » [87753 sur 166016 bons de demande en hémostase (53%)] L'objectif fixé était un seuil de NC inférieur à 15% par mois pour ces 2 critères. Stratégie: Nous avons choisi deux services impliqués dans les démarches d'amélioration continue de la qualité : le service d'accueil des urgences et le service de médecine interne. Les actions correctives choisies consistaient essentiellement en la réalisation de réunions de formation et d'informations des personnels de ces services (médecins et infirmières), en insistant sur la nécessité et les conséquences du remplissage correct des bons de demande, sur la qualité et la fiabilité du rendu de résultats. Le cycle des réunions (1 par mois de janvier 2008 à juin 2008) permettait également d'informer ces services du suivi de leur taux de NC et des améliorations observées. Résultats: Le suivi des taux des NC, pour ces deux services, est résumé ci-dessous. Suivi des NC pour le critère #1 "dates et heures de prélèvement non renseignées": Service d'accueil des urgences: mois 1 (32%), mois 12 (27%), mois 24 (18%) Service de médecine interne: mois 1 (45%), mois 12 (27%), mois 24 (6%) Suivi des NC pour le critère #2 "traitement non renseigné": Service d'accueil des urgences: mois 1 (41%), mois 12 (45%), mois 24 (40%) Service de médecine interne: mois 1 (75%), mois 12 (85%), mois 24 (75%) Bilan : Critère #1: très nette amélioration du taux de conformité, toujours observé en 2009 Critère #2: persistance d'un taux élevé de NC : une autre stratégie d'action corrective est envisagée, passant par le recours à la prescription connectée. Conclusion: Fournir des résultats objectifs permet de convaincre médecins et infirmières de la nécessité de l'amélioration des pratiques. Suivre ces tableaux de bord dans le temps permet d'ancrer ces actions d'amélioration dans le temps. Sensibiliser les personnels des services cliniques n'a pas été suffisant pour diminuer le taux de NC du critère #2. Une analyse plus exhaustive des causes « racines » par la méthode RCA nous permettra certainement d'atteindre notre objectif.